The first forty days : the essential art of nourishing the new mother - Ou, Heng (Stewart, Tabori & Chang, 2016)
Emphasizes the importance of the first forty days after childbirth for mothers, describing traditions and rituals, as well as providing recipes designed to restore vitality, including oxtail stew and seasonal greens soup.--